(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study investigates the linguistic features of idioms in English, Russian, and Uzbek, analyzing their similarities, differences, and cultural foundations. The research further examines the contemporary use of idioms on social media platforms and evaluates the capability of artificial intelligence (AI) systems to recognize, interpret, and generate idiomatic expressions. Using a comparative approach, the study identifies universal cognitive mechanisms behind idiomatic expressions as well as language specific cultural connotations. The results indicate that social media accelerates the spread of English idioms, which are often adapted in Russian and Uzbek contexts, while AI demonstrates partial understanding of idiomatic meaning, especially for culturally bound expressions. The findings contribute to phraseology studies and digital linguistics, providing insights for AI language processing and cross-cultural communication.